Predictors of participation and quality of life following major traumatic injuries in childhood: a systematic review. Issue 12 (5th June 2022) - Greenham, Mardee; Botchway, Edith; Knight, Sarah; Bonyhady, Bruce; Tavender, Emma; Scheinberg, Adam; Anderson, Vicki; Muscara, Frank
Abstract: Objective: Review the literature on predictors of participation and quality of life in children and young people who sustained a traumatic brain injury (TBI), spinal cord injury (SCI), and/or multi-trauma in a motor vehicle or other accident or trauma. Design: This systematic review was conducted and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The protocol was registered on PROSPERO (registration number CRD42020131698). Electronic databases were searched for studies published between January 2000 and August 2020. Prospective and retrospective cohort studies were considered and risk of bias was assessed using the Quality In Prognosis Studies (QUIPS) tool. Results: The search yielded 5771 articles of which 30 studies met the inclusion criteria. Nineteen studies included patients with TBI and 11 with SCI. No studies of patients with multi-trauma met criteria. Evidence was found for associations with various factors (e.g., injury severity, level of education, mental health problems), although these findings are limited due to the quality of the studies (5 studies moderate and 25 high risk of bias). Conclusion: Research on predictors of participation and quality of life following major traumatic injuries in childhood is lacking. More methodologically sound prospective, longitudinal studies are needed across different injury groups to further elucidate predictors of outcome. IMPLICATIONS FOR REHABILITATION: While long-term participation and quality of life is influenced by injury characteristics (i.e., injury severity), a number of potential modifiable factors can be targeted to improve outcomes following traumatic injuries in childhood. Young people should be provided with support to stay in school and pursue further education. Early intervention and prevention of mental health problems may improve long-term outcomes. Better management of ongoing medical problems and greater support for functional independence may improve participation.